Performances in the Ritual to Worship Chao Pho Mahesak - Chansaengsri, Angkana; Lajunnon, Parichat; Meepiam, Chanpim (Journal of Fine and Applied Arts Khon Kaen University, 2024)
Research article on performance in the ceremonial dance to honor Chaopho Mahesak The objective is to study the history of performances. Legend of Chao Pho Mahesak, Ban Tiew Subdistrict, Lom Sak District, Phetchabun Province and study performances in rituals using research methods or research processes (methodology) by using qualitative research methods (qualitative research) The results of the research found that the Khaeb Lan dance performance Influenced by the spread of culture from Vientiane, the capital of Laos. Chao Pho Mahesak or Chao Fa Ta Fai Has it existed since any time? There is no clear evidence. It is just a legend, a folk story. The performance has local cultural attire including: 1. Black cylinder sleeve shirt. 2. Pearl-patterned sarong 3. Nails 4. Belt 5. Bell 6. Red headdress 7. Black glasses. Musical instruments include 1. drum, 2. cymbals, 3. cymbals, 4. gongs, 5. cane, no gender restrictions and Age of the performer Ritual analysis Structure of the ritual Contains a specified day and month It is a traditional northern performance. The method of performance has 3 poses: 1. Salutation pose 2. Upward flick pose 3. Side flick pose.